The Role of Perceived Strategic Planning in Enhancing School Effectiveness in Public Secondary Schools - Sheyin, Adejoke Olabisi (Mimbar Ilmu, 2024)
School effectiveness is one of the critical factors determining the quality of education. However, in public secondary schools in Ogun State, Nigeria, school effectiveness remains low, as reflected in poor teacher performance, low teaching quality, and inefficient school operations. This study aims to analyze the role of perceived strategic planning in improving school effectiveness. The study employed a descriptive survey design with a quantitative approach. The population included 20,000 public secondary school teachers, with a sample of 400 teachers selected through a multi-stage random sampling method. Out of the selected sample, 360 respondents provided valid responses. The primary research instrument was a questionnaire developed by the researcher titled The Role of Strategic Planning in School Effectiveness in Public Secondary Schools Questionnaire (RSPSEPSSQ). Data were analyzed using descriptive statistics, including mean scores and standard deviations. The findings indicate that the practice of strategic planning in public secondary schools remains low, with a mean score of 1.79 ± 1.04. Similarly, school effectiveness was recorded as low, with a mean score of 1.68 ± 1.29. However, respondents acknowledged that the implementation of strategic planning practices significantly contributed to improving various school aspects, such as teacher performance, teaching quality, administrative efficiency, and collaboration among teachers, students, and administrators to achieve common goals, with a mean score of 2.86 ± 0.94. Based on these findings, it is concluded that public secondary schools in Ogun State implement professional development programs for school principals and administrators to enhance effective strategic planning practices.